Suberites syringella - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites syringella (Schmidt 1868) (Fig. 5a–d) Raspalia syringella : Schmidt 1868, p. 10, pl. II, fig. 9; Topsent 1938, p. 13. Suberites spec.: Vosmaer 1885, p. 21, pl. I, fig. 9a,b; pl. IV, fig. 33. Suberites glabra : Hansen 1885, p. 11, pl. II, fig.9. Suberites carnosus var. ramosus : Topsent 1900, p. 237, pl. VII, figs. 1, 2; Lundbeck 1909, pp. 453–454; Breitfuss 1911, p. 218; Breitfuss 1912, p. 74; Topsent 1913, p. 26; Topsent 1928, p. 155; Koltun 1964, p. 150; Rezvoi 1928, p. 82. Suberites carnosus : Hentschel 1929, p. 926. Pseudosuberites carnosus : Koltun 1966, p. 99, fig. 72, pl. XXXIII, figs. 3–4. Suberites syringella : Pulitzer-Finali 1978, pp. 24–25, figs. 2–3; Pulitzer-Finali 1983, p. 483; Voultsiadou-Koukoura and Van Soest 1993, pp. 182–183; Bertolino et al. 2015, pp. 1372–1373, figs. 2B,C & 3A–C. Material analyzed. Barents Sea, PINRO trawl survey, F. Nansen , 2005, st. 4 (78.0132N, 9.9735E), depth 163 m, temperature 3.93 °C, salinity 35.053 psu (9 specimens; KFU-LH-2/014); st. 16 (76.6442N, 13.5676E), depth 423 m, temperature 3.33 °C, salinity 35.08 psu (8 specimens; KFU-LH-2/015); st. 21 (75.9898N, 14.3593E), depth 373 m, temperature 3.29 °C, salinity 35.057 psu (4 fragments; KFU-LH-2/016). Muklevich , 2003, st. 5 (69.8658N, 31.1627E), depth 93.4 m, temperature 3.35 °C (1 specimen); st. 7, (69.9163N, 31.3416E), 1 specimen, KFU-LH-2/017. Description . The numerous fragments of this species are all of an elongated, cylindrical shape, with anastomosing side branches and rather broad basal attachment which, when intact, closely embrace small pebbles and stones (Fig. 5c). Conical oscula are scattered along the sides of branches. Surface smooth. The consistency is rather soft and delicate. Color pale yellow (in alcohol). Spicules . Tylo- and subtylostyles straight or slightly curved near the basal end of spicule, fusiform, rather short-pointed (Fig. 5a–b). Megascleres (choanosomal vs. ectosomal) not clearly distinguishable into two distinct size categories, vary in dimensions significantly: ...